POLITIK HUKUM TATA KELOLA PERTAMBANGAN TIMAH DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN DI PROVINSI KEPULAUAN BANGKA BELITUNG - Frans Tory Damara Pradipta (Universitas Tabanan, 2026)
This study aimed to analyze the legal politics of tin mining governance from the perspective of sustainable development in the Bangka Belitung Islands Province. The research focused on environmental degradation caused by tin mining activities, weak implementation of post-mining reclamation, and the lack of optimal supervision and law enforcement in mining activities. This study employed normative legal research using statutory, conceptual, and case approaches. The results showed that the legal politics of tin mining governance had tended to prioritize the exploitation of natural resources rather than environmental protection and social sustainability. This condition was reflected in the increasing number of critical post-mining areas, coastal environmental degradation, and the growth of illegal mining activities in the Bangka Belitung Islands Province. The study concluded that the reconstruction of mining legal politics should be directed toward strengthening sustainable development principles through the optimization of post-mining reclamation, strengthening environmental supervision, enforcing laws against illegal mining, and enhancing the protection of communities and the environment within mining policies.